Ginkgolide B Protects Against Ischemic Stroke via Targeting AMPK/PINK1 - Cao, Yile; Yang, Lei; Cheng, Hong (Frontiers in Pharmacology, 2022)
Introduction: Ginkgolide B (GB), which is an active constituent derived from Ginkgo biloba leaves, has been reported to ameliorate Alzheimer’s disease (AD), ischemic stroke, as well as other neurodegenerative diseases due to its viable immunosuppressive and anti-inflammatory functions. However, it has yet to be proven whether GB inhibits neuronal apoptosis in ischemic stroke. Methods: In the present research, the inhibition function of GB on neuronal apoptosis and its underpinning process(s) after cerebral ischemia were studied through transient middle cerebral artery occlusion (t-MCAO) in an in vivo rat model as well as in cultured SH-SY5Y cells subjected to oxygen and glucose deprivation (OGD)/reoxygenation in vitro. The neurological score was calculated and Nissl and TUNEL staining were performed to evaluate the stroke outcome, neuronal loss, and neuronal apoptosis. Subsequently, the western blot was utilized to detect Bcl2 and p-AMPK/AMPK expression. Results: Compared to t-MCAO rats, rats receiving GB treatment showed a significant reduction of neuronal loss and apoptosis and improved neurological behavior at 72 h after MCAO. GB treatment also upregulated the expression of Bcl2 and p-AMPK. In vitro, GB suppressed the apoptosis in OGD/reoxygenation-challenged neuronal SH-SY5Y cells through AMPK activation. Conclusions: Our observations suggest that GB enhanced AMPK activation in neural cells, reducing neuronal apoptosis, thus eventually preventing ischemic stroke.